2009
DOI: 10.1161/circinterventions.109.852665
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thrombus Aspiration on Myocardial Tissue Reperfusion and Left Ventricular Functional Recovery and Remodeling After Primary Angioplasty

Abstract: Background-Failure to achieve myocardial reperfusion often occurs during percutaneous coronary intervention (PCI) in patients with myocardial infarction with ST-segment elevation. We hypothesized that manual thrombus aspiration during primary PCI would favorably influence tissue-level myocardial perfusion and left ventricular (LV) functional recovery and remodeling. Methods and Results-We prospectively randomized 111 patients with ST-segment elevation myocardial infarction to either standard or thrombus-aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…22 Among the different strategies to limit the no reflow phenomenon, that of reducing distal embolization with a manual thrombus aspiration device is promising. 23 Despite the logical advantage of thrombus aspiration during PCI, however, a previous early study failed to confirm superiority of this approach in reducing infarct size or death rates. 24 A recent large, single-center, randomized trial and meta-analysis showed that manual thrombus aspiration is associated with a significant improvement in myocardial perfusion and reductions in shortand long-term mortalities in patients treated with primary PCI, but whether such improvements in myocardial reperfusion and TIMI flow grades in the pre-and post-lasing or aspiration angiograms and the final angiogram are shown in Figure 2, and MBG and STR are shown in Figures 3,4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…22 Among the different strategies to limit the no reflow phenomenon, that of reducing distal embolization with a manual thrombus aspiration device is promising. 23 Despite the logical advantage of thrombus aspiration during PCI, however, a previous early study failed to confirm superiority of this approach in reducing infarct size or death rates. 24 A recent large, single-center, randomized trial and meta-analysis showed that manual thrombus aspiration is associated with a significant improvement in myocardial perfusion and reductions in shortand long-term mortalities in patients treated with primary PCI, but whether such improvements in myocardial reperfusion and TIMI flow grades in the pre-and post-lasing or aspiration angiograms and the final angiogram are shown in Figure 2, and MBG and STR are shown in Figures 3,4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the use of a mechanical device for thrombus removal or trapping to improve clinical outcomes after p-PCI is attractive, and the efficacy of these devices has been tested in many clinical trials. Although some data, especially those regarding the use of distal protection devices, have failed to show clinical benefits due in part to patient and device selection [48][49][50][51][52][53] , many recent large-scale randomized trials have demonstrated significant improvements in myocardial perfusion 45,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the left ventricular function 64,65) in addition to reduced mortality 68) ( 69) . In addition, Burzotta et 70) .…”
Section: Thrombus Aspiration/distal Protection Therapy and Its Efficacymentioning
confidence: 99%
“…To test whether aspiration devices lead to better outcomes compared with standard PCI, we repeated the meta-analysis including only trials that used aspiration. [12][13][14][15][16][17][18][19][20]23,27,28,30,34,35,37 …”
Section: Thrombectomy Devicesmentioning
confidence: 99%